Inquiry-based learning for faculty and institutional development a conceptual and practical resource for educators - Carfora, John M.; Blessinger, Patrick (Bingley, U.K. : Emerald, 2014)
Inquiry-based learning (IBL) is a learner-centered and active learning environment where deep learning is cultivated by a process of inquiry owned by the learner. IBL has its roots in a constructivist educational philosophy and it is oriented around at least three components: 1) exploration and discovery (e.g., problem-based learning), 2) authentic investigations using contextualized learning (e.g., field studies), and 3) research-based approach (e.g., research-based learning). IBL encourages more self-regulated learning because the primary responsibility is on the learners to determine the issues and research questions and the resources they need to address the questions. In this way, learning occurs across all learning domains (affective, cognitive, and social) because different types of knowledge are acquired though experience with complex, real-life problems. This volume covers the many issues and concepts of how IBL can be applied to faculty and institutional development, serving as a conceptual and practical resource and guide for educators offering practical examples of IBL in action and diverse strategies for how to implement IBL in different contexts.
Innovative approaches in teaching and learning : an introduction to inquiry-based learning for faculty and institutional development / Patrick Blessinger, John M. Carfora -- A theoretical model of collaborative inquiry-based group development process / Diana J. Wong-MingJi, Gina N. Wong -- Strategies for transforming and extending inquiry-based teaching and learning : placers : a new model for transformative engagement and educator collaboration / Cheresa Greene-Clemons, Kisha N. Daniels -- The international baccalaureate : contributing to the use of inquiry in higher education teaching and learning / Tanya Chichekian, Bruce M. Shore -- Reframing relationships between teachers, students and curriculum : the phenomenon of 'hybridisation' in IBL / David Leat, Ulrike Thomas, Anna Reid -- Ways of inquiry : the distinctiveness of the Oxford college general education program / Jeffery Galle ... [et al.] -- Targeting students' epistemologies : instructional and assessment challenges to inquiry-based science education / Maggie Renken, Carmen Carrion, Ellen Litkowski -- Strategies for embedding inquiry-based teaching and learning in botanic gardens : evidence from the inquire project / Elaine Regan ... [et al.] -- Representation construction : a directed inquiry pedagogy for science education / Peter J. Hubber -- The graduating project : a cross-disciplinary inquiry-based capstone in arts / Andrew Funston, Nicolette Lee -- Creating an 'emporium of wonder' at Manchester museum / Menaka Munro, Hannah-Lee Chalk -- Engaging students in scientific inquiry : successes and challenges of engaging non-science majors in scientific inquiry / Amie K. Patchen ... [et al.] -- Mighty negatrons and collective knitting : academic educators' experiences of collaborative inquiry-based learning / Alicia Prowse -- How to scale inquiry-based teaching and learning through progressive faculty development / Tracy Miller -- Inquiry-based service learning in a university-based educational leadership program : service leadership and internship in a principal fellows program / R. Martin Reardon -- Confident voices : how professional development for teachers by teachers using video promotes inquiry-based practice / Michelle R. Edgcomb, Sherri J. Morris, Kelly D. McConnaughay -- Tools of engagement project (TOEP) : online professional development through structured inquiry and a virtual community / Roberta (Robin) Sullivan ... [et al.] -- Lessons from the field : using inquiry-based learning for study abroad programming / Paige E. Sindt, James M. Lucas -- Understanding the use of technology for facilitating inquiry-based learning / Jaimie Hoffman, Jill Leafstedt -- Supporting equality of education through inquiry-based learning / Joseph O'Shea, Latika L. Young.
Includes indexes.
Print version record
Keywords: Education -- General; Education; Open learning, home learning, distance education; Inquiry-based learning